2018
DOI: 10.4102/pythagoras.v39i1.393
|View full text |Cite
|
Sign up to set email alerts
|

Beyond test scores: A framework for reporting mathematics assessment results to enhance teaching and learning

Abstract: In this article we propose a framework for reporting mathematics results from national assessment surveys (NAS) such that effective use of the resulting reports can enhance teaching and learning. We explored literature on factors that may contribute to non-utilisation of assessment data as a basis for decision-making. In the context of South Africa, we identified the form and formats in which results of NAS are reported as a possible limiting factor to the effective use of summative assessment results for form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…As such, individual feedback sessions with learners in difficulties are rare. Likewise, Naylor & Sayed (2014), Moloi & Kanjee, (2017) explains that inadequate teacher preparation and support, large classrooms, lack of resources and entrenched cultural and pedagogical practices hamper the process of changing teaching styles in Africa. Govender (2019) argues that some teachers in South Africa who have completed Assessment for Learning trainings experience difficulties integrating formative assessment in their daily practice.…”
Section: Resultsmentioning
confidence: 99%
“…As such, individual feedback sessions with learners in difficulties are rare. Likewise, Naylor & Sayed (2014), Moloi & Kanjee, (2017) explains that inadequate teacher preparation and support, large classrooms, lack of resources and entrenched cultural and pedagogical practices hamper the process of changing teaching styles in Africa. Govender (2019) argues that some teachers in South Africa who have completed Assessment for Learning trainings experience difficulties integrating formative assessment in their daily practice.…”
Section: Resultsmentioning
confidence: 99%
“…However the utility of this information for identifying specific learning needs of students, or determining the specific sets of knowledge and skills that students master, is limited (Bond & Fox, 2007;Montgomery & Connoly, 1987). Raw scores on their own cannot be used qualitatively to indicate what students were able or not able to do in a test (Bond & Fox, 2007;Moloi & Kanjee, 2018). Raw scores, including percentages, are sample-and test-dependent.…”
Section: Typical and Additional Forms Of Reporting Assessment Resultsmentioning
confidence: 99%
“…The choice of the OSS method was informed by our research that indicates this method as being both cost-effective and providing curriculum-rich information for meaningful reporting of assessment results. Interested readers can refer to Moloi and Kanjee (2018) for general procedures of standard setting and to Stone (2001) for specific technical procedures of the OSS method. The information gathered from the standard setting session was used to conduct an intensive audit of the knowledge and skills that characterise students at each performance level to establish the PLDs.…”
Section: Development Of Performance Levels and Performance Level Descriptorsmentioning
confidence: 99%
See 1 more Smart Citation
“…This paper is situated within the literature on assessment-particularly assessment purposes and utility to improve teaching and learning. Moloi and Kanjee (2018) reported that a challenge facing South African teachers is the inadequacy of meaningful reporting and effective utilisation of evidence from assessment. They argued that meaningful reporting includes finding effective ways of converting raw data into information that can inform decision-making and explained: At classroom level, "meaningful information" refers to information that the teacher could use for determining what learners at a particular grade level know or do not know, and can or cannot do, and to develop relevant interventions to address specific learning needs of learners.…”
Section: Introductionmentioning
confidence: 99%